Arthroscopic Treatment of 2 Consecutive Cases of Dysplasia Epiphysealis Hemimelica of the Ankle: A 5-Year Follow-Up Report. (30th May 2017) - Calderaro, Cosma; Iorio, Carlo; Turturro, Francesco; Morelli, Federico; Labianca, Luca; Montanaro, Antonello; Ferretti, Andrea
Abstract : The dysplasia epiphysealis hemimelica (DEH) is a rare disease of unknown etiology consisting in an abnormal osteocartilaginous growth at the epiphysis, usually hemimelic with histological findings similar to benign osteochondroma. In this case series, we described the results of the arthroscopic treatment of 2 consecutive cases of intra-articular ankle localization of DEH in 2 patients aged 9 and 10 years. The good result obtained, persistent at the 5-year follow-up, leads us to consider the arthroscopic approach as a reliable treatment in patient affected by intra-articular ankle DEH.